Investigation of the Effects of Nanoparticle Concentration and Cutting Parameters on Surface Roughness in MQL Hard Turning Using MoS2 Nanofluid - Ngo Minh Tuan (MDPI AG, 2021)
Minimum quantity lubrication (MQL) has gained significant attention in various research fields and industrial applications for its advantages of being environmentally friendly and suitable for sustainable production. The effectiveness of MQL is increasing significantly by using nano cutting fluid, which can be produced by suspending nanoparticles in the based cutting fluid. This study aims to investigate the effects of MoS2 nanoparticle concentration, cutting speed, and feed rate on MQL hard turning of 90CrSi steel in terms of surface roughness and surface microstructure. The Box–Behnken experimental design was used to analyze the influence of input parameters and their interaction effects as well as to find the optimal set of variables. The obtained results prove the improvement of the machinability of carbide tools due to higher cooling and lubricating performance created by MoS2 nanofluid MQL, which contributes to improve the surface quality and reduce the manufacturing cost. There is an interaction effect between nanoparticle concentration and feed rate which has a strong influence on surface roughness.